Application of Value Stream Mapping to Improve the Production Process in Motorcycle Parts Manufacturing Industry - Wonginta, Thitima; Hlongsawat, Krit (Business Administration and Management Journal Review, 2023)
The goal of this study was to explore the approach for reducing the amount of work in process waiting in the production of motorcycle parts and improve the production process to be more efficient. The research began with the production process investigation, collection of the production volume data, followed by applying cause and effect diagram to prioritize products with the highest volume for analysing using value stream mapping. Then examined the causes of waste in the production process using fishbone diagram and proposed solutions to improve the manufacturing process, as well as examined the value stream mapping in the future state. The researchers selected four models of Crank Shaft product that the highest production volume. The results revealed that there were four locations where the number of working process parts waiting during the production process was high. The researchers investigated the cause of problem by using fishbone diagram and proposed solutions to improve the production process. The results from the improvement of production process showed that the entire processing time fell by 5.6 percent, from 618 to 583 minutes, and the production lead time decreased by 40.47 percent, from 18.21 to 10.84 days.